21ST CENTURY TECHNOLOGY INFLUENCES ON PEDAGOGY AND LEARNING STYLES’ RESEARCH - Celli, Lynne M (PEOPLE: International Journal of Social Sciences, 2019)
Twenty-first education learning and teaching must include application of research that meets the needs of all students with different diverse learning styles. Historically, instructors understand and implement instructional strategies that are connected to the current research about learning styles. Additionally, all instructors must now point to the current educational technology and how this new technology must be included in developing and application of activities/lessons that also address these diverse learning style. In addition, it is important to also provide this specific type of pedagogy to expand typical teaching strategies in order to make additional modes of learning available to all students. This interactive article will address the ways that learnings styles research can be connected in practical ways with 21st century contemporary technology to assure academic success for all.